The Public Prosecution Authority and its impact on saving money, a comparative study Saudi Arabia is a model - Alammari, Khalid Saleh; Qudah, Musa Mustafa (Journal of Islamic Sciences, 2022)
This study aimed to clarify the role of the Saudi Public Prosecution and its impact in achieving the purposes of preserving money compared to Islamic law. The researcher followed the descriptive, analytical and comparative approach, by explaining the meaning of money and the purposes of Sharia in its preservation, existence and non-existence. It employs specialized judges, and the Kingdom grants them judicial immunity, and their positions are public prosecutors.The Saudi system complies with the provisions of Sharia in obtaining money by legitimate means, and developing legal means that would preserve money in existence and non-existence, which was reflected in the preservation of money, through the application of Sharia provisions, to crimes of theft and destruction, and infringement on funds that It works on disciplining and deterring the offender, as well as reprimanding and deterring anyone who asks himself for it. Punishment has the effect of curbing and deterring the limited and others.
Keywords: behalf; body; money; preservation; existence; non-existence